2009
DOI: 10.1111/j.1743-6109.2008.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term, Multicenter Study of the Safety and Efficacy of Topical Alprostadil Cream in Male Patients with Erectile Dysfunction

Abstract: Introduction Alprostadil is approved for treatment of male erectile dysfunction (ED) by injection or urethral insertion. Topical delivery of alprostadil offers an improved alternative. Aim To evaluate the long-term safety and efficacy of topical alprostadil cream. Methods This was a multicenter, open-label, long-term study in 1,161 patients (998 double-blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…In contrast, common local AEs with alprostadil cream include penile burning sensation (25%) and penile erythema (11%). Furthermore, AEs leading to discontinuation were rarely reported with alprostadil cream: 4.3% were reported in clinical trials [Rooney et al 2009] compared with 12% with PDE5 inhibitors [Jiann et al 2006] and over 40% with PGE1 intracavernous injections [Hatzimouratidis et al 2015]. (4) Furthermore, the results of a survey of patients (n = 152) asked to express their preferences for an ED treatment according to the route of administration (systemic/ oral, injectable, intraurethral, or cream/ topical) showed that 53% of subjects would select a cream as the first choice [Moncada and Cuzin, 2015].…”
Section: Clinical Experiencementioning
confidence: 99%
“…In contrast, common local AEs with alprostadil cream include penile burning sensation (25%) and penile erythema (11%). Furthermore, AEs leading to discontinuation were rarely reported with alprostadil cream: 4.3% were reported in clinical trials [Rooney et al 2009] compared with 12% with PDE5 inhibitors [Jiann et al 2006] and over 40% with PGE1 intracavernous injections [Hatzimouratidis et al 2015]. (4) Furthermore, the results of a survey of patients (n = 152) asked to express their preferences for an ED treatment according to the route of administration (systemic/ oral, injectable, intraurethral, or cream/ topical) showed that 53% of subjects would select a cream as the first choice [Moncada and Cuzin, 2015].…”
Section: Clinical Experiencementioning
confidence: 99%
“…SEP2 -Were you able to insert your penis into your female partner's vagina?, SEP3 -Did the erection allowed you to have a satisfactory sexual intercourse?, was observed in the group of men taking the dose of 300 µg. Accordingly 80.3% and 61.1% of men gave positive answers to questions SEP2 and SEP3 at the end of the study, whereas during the first appointment (after taking 200 µg of alprostadil for 30 days), this percentage was 65.8% and 46.9%, respectively [39].…”
Section: Alprostadil In Creammentioning
confidence: 99%
“…The efficacy of the preparation was assessed in both short-term and long-term studies. The efficacy of alprostadil in cream administered initially for 4 weeks at the dose of 200 µg and then at the modified dose of up to 100 µg, 200 µg or 300 µg depending on the response of the patient to the treatment which was continued twice a week for up to 9 months was assessed in the open-label, multicentre study [39]. 75% of men chose the dose of 300 µg as the final dose, which was administered every 4-7 days.…”
Section: Alprostadil In Creammentioning
confidence: 99%
See 1 more Smart Citation
“…12 For the first 28 days, patients could administer eight doses of 200 mg alprostadil cream; for the next nine months, patients then self-selected to continue to administer the 200 mg cream, or to switch to administering 300 mg or 100 mg cream, based on their perceived therapeutic response. About one patient in eight (12%) of patients discontinued due to hypo-/hyper-responsiveness and <5% discontinued because of adverse effects (application site erythema in 12%, meatal or glans pain in 4% and prolonged or painful erection in 1.3%), and only five patients reported priapism; 2.1% of partners reported vaginal burning or pruritus.…”
Section: Clinical Experiencementioning
confidence: 99%